Evaluation of Food Hygienic Practices Training on Knowledge, Attitude, and Practice: A Study on Traditional Rambak Production in Berkah Enterprise - Adi Magna Patriadi Nuhriawangsa; Lilik Retna Kartikasari; Winny Swastike; Aqni Hanifa; Bayu Setya Hertanto (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2023)
Rambak (hide’s cracker) produced by small and medium-scale local communities still relies on production processes that have been passed down from generation to generation, resulting in minimal application of information and technology related to food safety. Thus, training in food hygienic practices needs to be carried out on different food handlers in order to provide an overview of the level of success of a program. This research aims to evaluate the impact of food hygienic practices training on knowledge, perception, attitude, and practice of food handlers in producing rambak. Training activities were carried out at the rambak production site involving 14 workers. The training process included presentations of raw materials (hides), rambak qualities, and good hygienic practices, then it was followed by demonstrations of good hygiene practices. Furthermore, the workers put into practice the work method demonstrated by the team. The assessment of knowledge, attitudes, and practices using questionnaire were carried out before and after the training. After training, the majority of rambak workers understand how to use raw materials and food hygiene practices, but they lack knowledge about packaging aspects and good rambak quality, such as washing fresh ingredients with tap water. Worker attitudes show that they have positive attitudes toward good hygiene practices, with the exception of touching food with bare hands. Food hygiene practice demonstrates that they had good hygienic practices, but they did not separate raw materials from cooked rambak. The effect of food hygiene practices training on internal characteristics demonstrates that workers' attitudes improved significantly (p<0,05), but not their knowledge and practice of hygienic principles. In summary, several aspects of worker characteristics need to be improved includes knowledge, attitude, and practice of food hygiene. The training effect improved rambak workers' attitudes but did not improve their knowledge or practice of hygienic principles